Implementasi Sistem Informasi dan Strategipada Industri Travel di Kota Yogyakarta - Fauzy Besta Pratamayuda; Fitriati - Akmila (Universitas Kristen Maranatha, 2018)
Information System are series of activities that process data becoming information. Strategy are plans made to achieve goals. The purpose if this research is to investigate the implementation of information system with information technology, management information system, accounting information system and the strategies implemented by the travel industries in the city of Yogyakarta in facing online travel agents. This research is a qualitative descriptive research with interview and observation for data collection. The results of this research shows that travel industries already use information system and strategies well. For the business process in each travel industries, they already use information system although the system is not yet integrated. Moreover, selling strategies they took has influenced their sales though they did not reached their profit target.Keywords: Travel Industries, Information Technology, Information Systems, Strategies